Art as a Political Witness - Lindroos, Kia; Möller, Frank (Verlag Barbara Budrich, 2017)
The book explores the concept of artistic witnessing as political activity. In which ways may art and artists bear witness to political events? The Contributors engage with dance, film, photography, performance, poetry and theatre and explore artistic witnessing as political activity in a wide variety of case studies.